REACTIVATION OF FERRIC OXIDES IN ROTARY FURNACES - S. L. Rovin; L. E. Rovin; T. M. Zajats (Литьë и металлургия)
The advantages of rotary furnaces, developed by specialists of GGTU named after P. O. Suhoj and UP «Tehnolit» for carrying out of ferric oxide recycling with regard to conditions of the Republic of Belarus, are described.